The case for reviving securitization - Markus Demary (Institut der deutschen Wirtschaft (IW), 2016)
European financial markets are still fragmented. A lack of cross-border lending and cross-border asset holdings hinders the financing of the economy, the conduct of monetary policy as well as cross-border risk-sharing against asymmetric shocks. Reviving the market for securitizations is vital for achieving these goals. A true European Capital Markets Union is needed, but there are still a lot of obstacles to overcome.
Keywords: 330